Moderated Basicity of Endohedral Amine Groups in an Octa‐Cationic Self‐Assembled Cage. (26th January 2022) - Ngai, Courtney; Wu, Hoi‐Ting; da Camara, Bryce; Williams, Christopher G.; Mueller, Leonard J.; Julian, Ryan R.; Hooley, Richard J.
Abstract: A self‐assembled Fe II 4 L6 cage was synthesized with 12 internal amines in the cavity. The cage forms as the dodeca‐ammonium salt, despite the cage carrying an overall 8+ charge at the metal centers, extracting protons from displaced water in the reaction. Despite this, the basicity of the internal amines is lower than their counterparts in free solution. The 12 amines have a sliding scale of basicity, with a ≈6 p K a unit difference between the first and last protons to be removed. This moderation of side‐chain basicity in an active site is a hallmark of enzymatic catalysis. Abstract : An endohedrally functionalized self‐assembled Fe4 L6 cage complex with 12 internal amines in the cavity acts as an acid host, and shows differential basicity, moderated by the cage superstructure.